2020
DOI: 10.1371/journal.pcbi.1007918
|View full text |Cite
|
Sign up to set email alerts
|

Classifying sex and strain from mouse ultrasonic vocalizations using deep learning

Abstract: Vocalizations are widely used for communication between animals. Mice use a large repertoire of ultrasonic vocalizations (USVs) in different social contexts. During social interaction recognizing the partner's sex is important, however, previous research remained inconclusive whether individual USVs contain this information. Using deep neural networks (DNNs) to classify the sex of the emitting mouse from the spectrogram we obtain unprecedented performance (77%, vs. SVM: 56%, Regression: 51%). Performance was e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Furthermore, we note that almost all recordings of the same individuals are co-localized, indicating that within-subject differences in syllable repertoire are smaller than those between individuals. Although it has been previously shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy ( Ivanenko et al, 2020 , Figure S1), here we find that repertoire features learned in a wholly unsupervised fashion achieve similar results, indicating that mice produce individually stereotyped, stable vocal repertoires.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…Furthermore, we note that almost all recordings of the same individuals are co-localized, indicating that within-subject differences in syllable repertoire are smaller than those between individuals. Although it has been previously shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy ( Ivanenko et al, 2020 , Figure S1), here we find that repertoire features learned in a wholly unsupervised fashion achieve similar results, indicating that mice produce individually stereotyped, stable vocal repertoires.…”
Section: Resultssupporting
confidence: 45%
“…Finally, we used a much larger library of female-directed mouse USVs (36 individuals, 2-4 20minute recording sessions each, 40 total hours of audio, 156,000 syllables) to investigate the diversity and stability of syllable repertoires. We repeated the above procedure, estimating MMD for shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy (Ivanenko et al (2020), Figure S1), here we find that repertoire features learned in a wholly unsupervised fashion achieve similar results, indicating mice produce individually-stereotyped, stable vocal repertoires.…”
Section: Latent Spaces Facilitate Comparisons Between Vocal Repertoiresmentioning
confidence: 80%
“…Furthermore, we note that almost all recordings of the same individuals are co-localized, indicating that within-subject differences in syllable repertoire are smaller than those between individuals. Although it has been previously shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy ([19], Figure S1), here we find that repertoire features learned in a wholly unsupervised fashion achieve similar results, indicating mice produce individually-stereotyped, stable vocal repertoires.…”
Section: Resultssupporting
confidence: 40%
“…Mice produce ultrasonic vocalizations (USVs) in diverse social contexts ranging from courtship to aggression ( Sangiamo et al, 2020 ; Warren et al, 2020 ; Neunuebel et al, 2015 ). We tested DAS using audio from an intruder assay, in which an anesthetized female was put into the home cage and the USVs produced by a resident female or male were recorded ( Ivanenko et al, 2020 ). The female USVs from this assay typically consist of pure tones with weak harmonics and smooth frequency modulations that are often interrupted by frequency steps ( Figure 2A, B ).…”
Section: Resultsmentioning
confidence: 99%